Analysis on the Behavior Characteristics of NOx in Blast Furnace Gas - Peng HOU; Changliang ZHEN; Zibing WANG; Jie XU; Long HE; Xing ZHANG; Huan LIU (Kuangchan zonghe liyong)
This is an article in the field of metallurgical engineering. In order to reduce the NOx emission in the blast furnace smelting process, based on the analysis of the actual production data of the 2 300 m3 blast furnace in an iron and steel plant, this paper elaborates on the formation and reduction mechanism of NOx in the blast furnace, and the distribution characteristics and influence of NOx in the blast furnace through thermodynamic calculation, mathematical statistics and other methods. The main conclusions are as follows: NOx in blast furnace gas is mainly NO, accounting for more than 99%, only a very small amount of NO2 and the temperature is the main factor affecting the formation of NOx at the front end of the raceway. When the temperature increases from 2 000 °C to 2 500 °C, the theoretically generated content of NO and NO2 increases by 2.56 and 1.7 times, respectively, and the key to controlling the reduction of NOx in blast furnace gas is to control the reasonable distribution of gas flow in the furnace. The gas flow should flow through the middle ring zone as much as possible at the basic requirements of gas flow distribution in the center and edge, and the reducing atmosphere in the normal smelting blast furnace can meet the full reduction of NOx, and the NOx emission level of downstream gas users at special furnace conditions such as deficit scale, hanging, blowing-down and reblowing should be paid attention to.